Description of Math Learning Difficulties in Mental Retardation Students in Completing the Original Number Calculation Operation - Hedia Rizki; Lovi Leoni (Journal of Curriculum and Pedagogic Studies (JCPS), 2022)
Learning difficulties are also faced by mental retardation students who attend educational programs in special schools. Although learning has been adjusted to the abilities of students using a special education curriculum, taught by teachers who have a special educational background, and grouped according to specificity. Students still have difficulties, one of which is students with a specificity of mental retardation. So it is necessary to know what difficulties are faced by students with mental retardation so that these difficulties can be overcome. This study is descriptive qualitative and aims to describe the learning difficulties faced by students with mental retardation in solving the problem of original number counting operations. As for the learning difficulties studied based on Lerner's theory, namely: (1) lack of understanding of symbols, (2) place values, (3) calculations, (4) incorrect use of processes, and (5) illegible writing. The instruments used consist of written test results and interview guidelines. The research subject selection technique used is purposive sampling. Research data obtained from the results of written tests and interviews analyzed based on learning difficulty indicators. The results of the study include, (1) STr cannot determine the value of the place correctly, and does not know the concept of place value. (2) STr has difficulty in summing the position of place values in a number symbol, associating place values with number symbols, and writing the results of addition and multiplication do not correspond to place values. (3) STr has difficulty in summation operations with the technique of storing and writing numbers in summation operations with a downward arrangement that does not pay attention to the value of the place. (4) STr has difficulty in calculating the multiplication problem because it tries to memorize the multiplication